The role of agriculture in Central and Eastern European rural development: engine of change or social buffer? - Martin Petrick; Peter Weingarten (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
This volume of proceedings, available both as hard copy and pdf <http://www.iamo.de/dok/sr_vol25.pdf>, is an edited compilation of selected contributions to the IAMO Forum 2004, which will be held in Halle (Saale), Germany, at the Institute of Agricultural Development in Central and Eastern Europe from 4 to 6 November 2004. CONTENTS: The role of agriculture in Central and Eastern European rural development: an overview; Martin Petrick, Peter Weingarten. Subsistence Farming and Rural Unemployment - the Case of Slovakia; Gejza Blaas. Rural Development in Albania and the Role of Agriculture: a Case Study in the Prefecture of Elbasan; Vittorio Gallerani, Nada Krypa, Meri Raggi, Antonella Samoggia, Davide Viaggi. Agricultural Problems in Georgia and Strategic Policy Responses; Zurab Revishvili, Henry W. Kinnucan. The Role of Private Household Plots in Russian Rural Development; Galina Rodionova. Agriculture in Southeastern Poland - Main Problems of The Systemic Transformation Process; Janusz Zmija, Ewa Tyran. Factor Market Imperfections and Polarization of Agrarian Structures in Central and Eastern Europe; Alexander Sarris, Sara Savastano, Christian Tritten. Agricultural Credit Market in Poland - Experiences in the Market Economy; Alina Danilowska. Social Aspects of Agricultural Employment in the Czech Republic; Hana Horská, Daniela Spěšná, Jan Drlík, Radomír Koutný, Tomáš Ratinger. Lease as a Form of Land Consolidation in Moldavian Agriculture; Dragos Cimpoies, Grigore Baltag. Analysing Variation in Russian Dairy Farms, 1990-2001; Irina Bezlepkina, Ruud Huirne, Alfons Oude Lansink, Arie Oskam. The Role of Agriculture for Rural Development in a less favoured Rural Area: The Experience of Mecklenburg-Western Pomerania (Germany); Theodor Fock. Wine, Sand and Socialism: Some enduring Effects of Hungary's 'Flexible' Model of Collectivization; Chris Hann. Off-Farm Activities and Subsistence Farming in CEE Countries - A Statistical Approach; Franz Greif. Agricultural Productivity Growth: a Vehicle For Rural Poverty Reduction in Ukraine? Viktoriya Galushko, Stephan von Cramon-Taubadel. Institutional Factors Influencing Agricultural Sales of the Individual Farmers in Romania; Borbala Balint. Social Capital in Rural Areas of Latvia within the Context of Public Organisations; Modrite Pelše. The Effects of Social Capital on the Organization of Agricultural Enterprises and Rural Communities in Transition: the Case of Ukraine; Vladislav Valentinov, Tetyana Matsibora, Mykola Malik. Farm Tourism: Myth or Reality? Štefan Bojnec. Biomass Production as a Future Agricultural Development Factor in West Pomerania (Poland); Jaroslaw Senczyszyn, Agnieszka Brelik. Rural Implications of Foreign Direct Investments in the Food Industry of the Visegrad Countries; Csaba Jansik. The Impact of Information Society on Agriculture and Rural Areas Development; Anton Nedyalkov, Victoria Borisova. Agricultural Policy and Rural Development: Theoretical and Empirical Aspects; Heinz Ahrens. A Tailor-Made Common Agricultural Policy for the Accession Countries: Help or Harm for Agriculture in Eastern Europe? David Sedik. Evaluation of the Effects of Pre-Accession and Accession Instruments on the Development of the Northeast Region in Bulgaria; Plamen Mishev, Antoaneta Golemanova. Measures of Rural Development Policy in Russia; Alexander Petrikov. Priority Setting for Rural Development: an Interactive PC-Based Programming Approach; Dieter Kirschke, Astrid Häger, Kurt Jechlitschka, Stefan Wegener
urn:nbn:de:gbv:3:2-5687
Keywords: 330